Pengaruh Piomi terhadap Feeding Skills pada Bayi Prematur di Rsud Koja Jakarta - Wasiah Kursius Samawati; Roy Romey Daulas Mangunsong; Alfiani Vivi Sutanto (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
This study aimed to examine the effect of the Premature Infant Oral Motor Intervention (PIOMI) on feeding skills in premature infants at RSUD Koja Jakarta, given that feeding skill dysfunction (mean gestational age 34.03 weeks) often leads to delayed oral feeding and prolonged hospitalization. Utilizing a one-group pretest-posttest quasi-experimental design, 30 premature infants were recruited via purposive sampling. The PIOMI intervention was administered intensively for 6 consecutive days, twice daily, starting at a mean chronological age of 6.8 days. Feeding skills were measured using the Early Feeding Skills Assessment Tool (EFSAT) before and after the intervention, and data were analyzed using the Paired Sample t-Test. Results showed that the mean EFS score significantly increased from 31.37 (pretest) to 47.17 (posttest), yielding a mean improvement of 15.8 points. The hypothesis test produced p < 0.001, indicating a highly significant effect of PIOMI. Furthermore, Cohen's d = 8.560 indicated a very strong, clinically relevant effect size (Very Large Effect). Functionally, 20% of subjects transitioned fully from OGT to oral feeding, and 43.3% increased their oral volume, accompanied by a mean weight gain from 1974.83 gr to 2049.23 gr. It is concluded that PIOMI is highly effective and has a strong clinical impact on improving feeding skills in premature infants, and its implementation as a standard protocol in the NICU is recommended to accelerate feeding independence.